Dari Imajinasi ke Presisi: Pelatihan Mental Imagery bagi Atlet Panahan Pelajar Kabupaten Maros - Muflih Wahid Hamid; Nukhrawi Nawir; Muhammad Rhesa; Reza Mahyuddin; Akbar Sudirman; Maudy Syahab (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2025)
Mental skills such as mental imagery play a crucial role in enhancing athletic performance, particularly in precision sports like archery. However, this skill is rarely introduced systematically to student-athletes at the regional level. This community service program aimed to introduce and train mental imagery skills among young female archers in Maros Regency, South Sulawesi Province. The activity was conducted on February 16, 2025, through a field-based training session involving 10 female athletes and two coaches. The intervention employed a participatory and practice-oriented approach that combined theoretical explanation, guided demonstrations, supervised exercises, and individual reflection. Evaluation through questionnaires and interviews indicated a significant increase in participants’ understanding of mental imagery and its perceived benefits in improving focus and concentration during training. The average scores across four assessment indicators were rated highly, with the highest score on positive experience (4.8 out of 5). This initiative demonstrates that community-based psychological approaches can be effectively implemented to strengthen the mental capacity of young athletes in regional areas.